Developing communicative skills-based reading materials for technical English course of Civil Engineering Study Program State Polytechnic of Malang - Tutuk Widowati (UPT P2M Politeknik Negeri Malang, 2011)
Reading is the most suitable skill in English for Specific Purposes (ESP) teaching and learning process. However, other skills should be accommodated in it. This study aims at developing appropriate communicative skills‐based reading materials for Technical English 1 (TE 1) Course at Civil Engineering Study Program (CESP) State Polytechnic of Malang. The proposed materials had to go through expert verifications and revisions. Then the revised materials experienced field try‐outs and revisions to be validated as a final product. A recycle was done to strengthen the validation. There are 7 units of reading developed based on Contextual Teaching and Learning (CTL) method, completed with appropriate learning activities and assessment techniques. The implementation of CTL approach has brought about betterment in the teaching and learning process of TE 1 Course for CESP students State Polytechnic of Malang.